Anthropometric and physiological characteristics in judo: Applicable for talent identification and development - Tojari, F.; Amini, A. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Each sport has specific means of talent identification that includes Testing and other related measurement. Tow specific means in talent identification are and anthropometric like stature to arms length, and physiological capabilities such as aerobic and anaerobic power. The purpose of this study is identification of physiological and anthropometric characteristics of male judo players, which is a useful help for talent identification for judo. result of This study shows a profile of anthropometrics and physiological aspects of elite level male judokas, The results of the research present as table that show the relation of each anthropometric parts to stature Also the table shows the important physiological characteristics of different weight categories in elite male Judokas. The data results of this research can be considered as a valuable model in talent identification and development in Judo through the country